Management of environmental noise - the Cracow example - CIESIELKA, Wojciech (Archives of Acoustics, 2007)
The aim of this article is describing the management of an environmental noise system. The main part of the system are information layers, which are based at a SoundPlan, Integrated Noise Model and MapInfo programs. The layers present maps of noise emitted by: road traffic, rail traffic, industrial activity sites and the airport Cracow - Balice. The strategic noise maps were performed according to the demands of the Directive of the European Parliament and of the Council of the European Union and National Law Acts. The System is working on available measurement data. It is impossible to eliminate environmental noise so it is necessary to reduce the number of noise exposed people. The problem is to get right information about the sources, levels of each source, the number of people living in a given are and the results of the noise reduction action. Every inhabitant should have the access to this information, especially when his decisions can affect the acoustical climate. From the other side, law makes it duty to serve noise pollution information to everybody (especially via internet). This article describes such a system which consists of two parts: database and presentation.